Perinatal depression before and during the COVID-19 pandemic in New York CityAJOG Global Reports at a Glance - Meralis Lantigua-Martinez, MD; Megan E. Trostle, MD; Anthony Melendez Torres, MD; Pournami Rajeev, BA; Alyson Dennis, BA; Jenna S. Silverstein, MD; Mahino Talib, MD (Elsevier, 2023)
BACKGROUND: Quarantining and isolation during previous pandemics have been associated with higher levels of depression symptomatology. Studies in other countries found elevated rates of anxiety and/or depression among pregnant people during the COVID-19 pandemic compared with prepandemic rates. New York City was the initial epicenter of the pandemic in the United States, and the effects of the pandemic on perinatal depression in this population are not well known. OBJECTIVE: This study aimed to evaluate the rates of perinatal depression before and during the COVID-19 pandemic. STUDY DESIGN: This is a single-center retrospective cohort study of patients screened for perinatal depression with the Edinburgh Postnatal Depression Scale at 2 private academic practices in New York City. This screen is done in these practices at the time of the glucose challenge test and at the postpartum visit. Patients aged ≥18 years who completed a screen at a postpartum visit and/or glucose challenge test from February 1, 2019 to July 31, 2019 and from February 1, 2020 to July 31, 2020 were identified, and the 2019 and 2020 groups were compared. The primary outcome was a positive screen, defined as ≥13 and ≥15 for postnatal and prenatal screens, respectively. Secondary outcomes included monthly changes in rates of positive screens and factors associated with perinatal depression. Data were analyzed using Mann-Whitney U test, chi-square, or Fisher exact test, and univariate and multivariate analyses with P<.05 defined as significant. RESULTS: A total of 1366 records met the inclusion criteria; 75% of the prepandemic (2019) records were included, as opposed to 65% of pandemic (2020) records due to a lower screen completion rate in the pandemic cohort. The 2020 cohort had a higher proportion of Hispanic patients (P=.003) and higher rates of diabetes mellitus (P=.007), preterm labor (P=.03), and current or former drug use (P<.001). The 2019 cohort had higher rates of hypertension (P=.002) and breastfeeding (P=.03); 4.6% of the 2020 cohort had a suspected or confirmed COVID-19 infection. There was no difference in perinatal depression between the 2019 and 2020 cohorts (2.8% vs 2.6%; P>.99). This finding persisted after adjusting for baseline differences (adjusted odds ratio, 0.89; 95% confidence interval, 0.38-1.86; P=.76). There were no differences in rates of positive Edinburgh Postnatal Depression Scale by month. Several risk factors were associated with a positive screen, including being unmarried (P<.001), pulmonary disease (P=.02), depression (P<.001), anxiety (P=.01), bipolar disorder (P=.009), and use of anxiolytics (P=.04). CONCLUSION: There were no differences in the rates of perinatal depression between the periods before and during the COVID-19 pandemic. The rate of perinatal depression in this cohort was below the reported averages in the literature. Fewer women were screened for perinatal depression in 2020, which likely underestimated the prevalence of depression in our cohort. These findings highlight potential gaps in care in a pandemic setting.